Identifying exercise-induced bronchospasm. Treatment hinges on distinguishing it from chronic asthma - Hermansen, C. L.; Kirschner, J. T. (The Physician and Sportsmedicine, 2005)
Exercise-induced bronchospasm (EIB) is an often-undiagnosed but common problem affecting both recreational and elite athletes. Although exercise can trigger exacerbation of chronic asthma, EIB should not be confused with the chronic inflammatory disease. In this article, Drs Hermansen and Kirchner review the incidence, diagnosis, and treatment of EIB and explain how to distinguish EIB from chronic asthma.